'It gives you the skills of how you can cope': Exploring the self‐reported experience of patients receiving in‐centre haemodialysis on participating in chosen art activities. (11th August 2021) - Taylor, Francesca; Drennan, Vari M.; Turner, Marie‐Louise; Jones, Jeunita; Popoola, Joyce
Abstract: Background: Increasing numbers of patients are receiving dialysis, particularly in high‐income countries. Patients receiving haemodialysis often experience fatigue, anxiety, depression and boredom. It is suggested that arts activities could have a therapeutic effect. Objective: This study aimed to explore patients' perspectives of participating while on dialysis in chosen arts and creative living activities provided by tutors at the bedside. Design: Qualitative semi‐structured interviews in the interpretive tradition were conducted, with thematic analysis. Setting and Participants: Fifteen patients of different ages, genders and ethnicities who participated in an arts activity while receiving haemodialysis in an inner‐city dialysis unit in England were included in this study. Results: Participants reported positive experiences of engaging in art activities. Their views on the value of the activities were grouped into five themes: diversion from receiving haemodialysis, a sense of achievement, contribution to a more positive self‐identity, increased confidence and motivation and a therapeutic talking relationship. Participants suggested that patient peer promotion of the activities could increase uptake, with patient choice of activity seen as important. Conclusions: Participation in a chosen arts activity while receiving haemodialysis was perceived by patients to have positive psychosocial effects. We theorize three potential explanatory mechanisms for these effects: That the experience of participating in the activities engendered positive psychological states of 'being in the flow'; enhanced self‐esteem to add to personal coping mechanisms; and offered additional facets to the patient's identity that countered the stigmatizing effect of receiving dialysis. Patient or Public Contribution: Patients and public representatives advised on the design, research methods and tools.